Expression of the Clonostachys rosea lactonohydrolase gene by Lactobacillus reuteri to increase its zearalenone-removing ability - Yang, Wen-Chun (Microb Cell Fact, 2017)
BACKGROUND: Mycotoxins are secondary metabolites produced by filamentous fungi that can contaminate agricultural crops in the field as well as during harvest, transportation, processing, or storage. Zearalenone (ZEN), a non-steroidal estrogenic mycotoxin, produced by Fusarium species, has been shown to be associated with reproductive disorders in farm animals and to a lesser extent in hyperoestrogenic syndromes in humans. Thus, the decontamination of ZEN in foods and feeds is an important issue. RESULTS: In this study, the gene encoding ZHD101, a ZEN-degrading enzyme produced by Clonostachys rosea IFO 7063, was cloned into an Escherichia coli–Lactobacillus shuttle vector, pNZ3004, and the resultant plasmid pNZ-zhd101 was then introduced via electroporation into Lactobacillus reuteri Pg4, a probiotic strain isolated from the gastrointestinal tract of broilers. The transformed strain L. reuteri pNZ-zhd101 acquired the capacity to degrade ZEN. In addition, the production of recombinant ZHD101 did not affect cell growth, acid and bile salt tolerance, and had only a minor effect on the adhesion ability of L. reuteri pNZ-zhd101. CONCLUSIONS: To the best of our knowledge, this is the first report of successful expression of a ZEN-degrading enzyme by intestinal lactobacilli.